Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fsufs.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

Use of Plant Growth-Promoting Rhizobacteria in Maize and Sugarcane: Characteristics and Applications

Abstract: Free-living bacteria that actively colonize plant roots and provide positive effects on plant development are called plant-growth promoting. Plant growth-promoting bacteria can promote plant growth and use their own metabolism to solubilize phosphates, produce hormones and fix nitrogen, and they can directly affect plant metabolism. PGPR also increase plant absorption of water and nutrients, improving root development and increasing plant enzymatic activity; moreover, PGPR can promote other microorganisms as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 201 publications
0
59
0
2
Order By: Relevance
“…However, potassium metabolism was more in the Ventersdorp rhizosphere (Figure 4(A)). Research studies on maize crops have shown that increased potassium metabolism arises from stimulation of root growth or elasticity of root hair by bacteria for plant growth and development (dos Santos et al 2020;Meena et al 2014;Singh et al 2010). The maize plants would have poorly formed roots without sufficient potassium availability, grow slowly, generate have lower crop yields and increase susceptibility to disease and pests (Meena et al 2014).…”
Section: Effects Of Soil Parameters On the Bacterial Community Structmentioning
confidence: 99%
“…However, potassium metabolism was more in the Ventersdorp rhizosphere (Figure 4(A)). Research studies on maize crops have shown that increased potassium metabolism arises from stimulation of root growth or elasticity of root hair by bacteria for plant growth and development (dos Santos et al 2020;Meena et al 2014;Singh et al 2010). The maize plants would have poorly formed roots without sufficient potassium availability, grow slowly, generate have lower crop yields and increase susceptibility to disease and pests (Meena et al 2014).…”
Section: Effects Of Soil Parameters On the Bacterial Community Structmentioning
confidence: 99%
“…PGPR also secrete abscisic acid, which stimulates growth activities under stress. It is secreted by many PGPR such as Azospirillum brasilense, Bacillus subtilis, Bacillus licheniformis, and Pseudomonas putida (Cohen et al, 2008;Dos Santos et al, 2020;Kousar et al, 2020). Ethylene is a gaseous hormone which controls fruit ripening (Masood et al, 2012;Nazar et al, 2014).…”
Section: Stenotrophomonas Maltophilia Sbp-9mentioning
confidence: 99%
“…The role of PGPR in solubilizing and oxidizing other essential plant nutrients, such as potassium, sulfur, and micronutrients, and their effects on plant growth-promotion are far less studied compared to N, P, and Fe. For more information regarding the role of PGPR in providing these elements to plants, the reader can consult recent publications on this topic [110,111].…”
Section: Enhanced Nutrient Acquisition (Biofertilizer)mentioning
confidence: 99%